PRACTICES AND AWARENESS OF PRIMARY SCHOOL TEACHERS ON SUSTAINABLE DEVELOPMENT GOALS-2030 (International Journal of Food and Nutritional Sciences, 2022)
The Sustainable Development Goals-2030 (SDGs), established by the United Nations, play a crucial role in shaping global development agendas and addressing social, economic, and environmental challenges across the universe. Education systems play a crucial role in developing sustainable practices among children by fostering awareness, knowledge, and skills essential for a sustainable future. Primary school teachers play a key role in preparing children by creating an environment where the child practices sustainability knowingly or unknowingly. Primary school teachers can enhance awareness about sustainability concepts by incorporating contents related to Sustainable Development into the curriculum, and thereby help students to understand the importance of sustainable practices in their day to day life. To handle this situation the primary school teacher should be aware about the various concepts, policies and different dimensions of Sustainable Development and the importance of sustainable life styles to be practiced in daily life to make a more sustainable world. The main objectives of the study were to identify the extent of awareness of primary school primary school teachers about the Sustainable Development Goals-2030, and to analyse lifestyle practices of primary school teachers in their decision making and day to day activities that support sustainable practices. Survey method was adopted for the study. The perception of primary school teachers about Sustainable Development Goals and their classroom practices were identified using a standardised tool prepared by the researcher. The survey was conducted among the primary school teachers of three districts, as a representation of the population, the primary school teachers of Kerala. 50 primary school teachers, each from Kannur, Thrissur, and Thiruvananthapuram were selected for the study. Primary school education plays a vital role in developing lifestyles through life practices in their daily life situations. For this the awareness regarding the Sustainable Development Goals-2030 and their practicing possibilities in the classrooms must be well familiar to the teachers. The findings of the study will help to identify the level of awareness on the concept of sustainable development in primary school teachers. Also the study will help to identify and include areas where special attention should be paid to develop interventions in primary school teacher training programs to address the importance of Sustainable Development Goals.